Pengaruh senam kegel terhadap intensitas penurunan nyeri dismenorea pada remaja putri di Kabupaten Serang - Putri, Dian Priharja; Nency, Olivia (UKInstitute, 2022)
Adolescence is an important period due to rapid physical, psychosocial, cognitive, and emotional growth, as well as sexual and reproductive maturity. In 2020, the incidence of dysmenorrhea in women worldwide was 90% with 10-16% suffering from severe dysmenorrhea. The symptoms they experience are not relieved and can increase the risk of endometriosis. Dysmenorrhea can significantly impact quality of life, and can even have a socioeconomic impact. Physical activity is one way that can be used to reduce the intensity of dysmenorrhea. This study is a pre-experimental design with a pretest-postest control group design. The sample was 100 grade VIII students who experienced menstruation with dysmenorrhea who were randomly selected from SMPN 1 Bandung, SMPN 2 Kibin, SMPN 1 Petir, and SMPN 3 Cikande in Serang Regency. The study was conducted in July 2022 which was divided into two groups, namely the group that did Kegel exercises and the group that did not do Kegel exercises. Kegel exercises were performed with a duration of 10-15 minutes when dysmenorrhea occurred. Dysmenorrhea pain scale was measured using Numerical Rating Scales (NRS). Analysis using T-Indepent Test with SPSS 27.0. There is a difference in pain levels in the group who do Kegel exercises with a group that does not do Kegel exercises in adolescent girls with a p-value = 0.037 (p less than 0.05). Kegel exercise affects the intensity of dysmenorrhea pain reduction in adolescent girls in Serang Regency.